Single and composite damage mechanisms of soil polyethylene/polyvinyl chloride microplastics to the photosynthetic performance of soybean (Glycine max [L.] merr.) - Li, Haibin; Song, Fupeng; Song, Xiliang; Zhu, Kongming; Lin, Qun; Zhang, Jinliang; Ning, Guoqiang (Frontiers in Plant Science, 2023)
Introduction Adverse impacts of soil microplastics (MPs, diameter<5 mm) on vegetative growth and crop production have been widely reported, however, the single and composite damage mechanisms of polyethylene (PE) /polyvinyl chloride (PVC) microplastics (MPs) induced photosynthesis inhibition are still rarely known. Methods In this study, two widely distributed MPs, PE and PVC, were added to soils at a dose of 7% (dry soil) to examine the single and composite effects of PE-MPs and PVC-MPs on the photosynthetic performance of soybean. Results Results showed PE-MPs, PVC-MPs and the combination of these two contaminants increased malondialdehyde (MDA) content by 21.8-97.9%, while decreased net photosynthesis rate (Pn) by 11.5-22.4% compared to those in non-stressed plants, PVC MPs caused the most severe oxidative stress, while MPs stress resulted in Pn reduction caused by non-stomatal restriction. The reason for this is the single and composite MPs stress resulted in a 6% to 23% reduction in soybean PSII activity RCs reaction centers, along with negative effects on soybean PSII energy uptake, capture, transport, and dissipation. The presence of K-band and L-band also represents an imbalance in the number of electrons on the donor and acceptor side of PSII and a decrease in PSII energy transfer. Similarly, PVC single stress caused greater effects on soybean chloroplast PSII than PE single stress and combined stresses. Discussion PE and PVC microplastic stress led to oxidative stress in soybean, which affected the structure and function of photosynthetic PSII in soybean, ultimately leading to a decrease in net photosynthetic rate in soybean.